2010
DOI: 10.1111/j.1744-7410.2010.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns of land flatworm assemblages in Brazilian Araucaria forests

Abstract: Abstract. Araucaria forests are among the most threatened biomes of one of the world's 25 biodiversity hotspots, the south Brazilian Atlantic Rain Forest. This study was focused on flatworm community structure in three protected areas located on the eastern border of the Araucaria Plateau in south Brazil. We addressed three main questions: (1) How species‐rich are Araucaria forests? (2) Are there any differences in the community structure within the three areas? (3) What is the distribution pattern of land fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
0
18
0
4
Order By: Relevance
“…franciscana and O. josefi, the first and third most dominant species in AMF, respectively, are among the five most abundant species in areas of Araucaria moist forest (Leal-Zanchet et al 2011). Their low dominance or abundance in AMF-P and P suggest that both may prefer preserved areas, which has already been indicated for P. franciscana (Carbayo et al 2002).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…franciscana and O. josefi, the first and third most dominant species in AMF, respectively, are among the five most abundant species in areas of Araucaria moist forest (Leal-Zanchet et al 2011). Their low dominance or abundance in AMF-P and P suggest that both may prefer preserved areas, which has already been indicated for P. franciscana (Carbayo et al 2002).…”
Section: Discussionmentioning
confidence: 88%
“…Land planarian communities are highly diverse in areas of Araucaria moist forest (Leal-Zanchet and Carbayo 2000; Baptista et al 2006;Fick et al 2006;Leal-Zanchet and Froehlich 2006;Antunes et al 2008;Leal-Zanchet and Baptista 2009;Leal-Zanchet et al 2011. They are important elements of forest communities and are considered to be top predators in their microhabitats, where they feed on other invertebrates, such as annelids, gastropods, insect larvae, other arthropods, and even other land planarians (Du Bois-Reymond Marcus 1951;Froehlich 1955;Ogren 1995;Jones and Cumming 1998;Winsor et al 1998;Sluys 1999;Carbayo and Leal-Zanchet 2003;Prasniski and Leal-Zanchet 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The species richness found in Ordesa and Picos may seem low if compared with similar studies performed in different Brazilian forests, where total flatworm species number ranges between 18 in areas of deciduous forests (De Castro & Leal‐zanchet, 2005) and 51 in areas of Araucaria forest (Leal‐Zanchet et al., 2011). Although these Brazilian species richness result from studies with different sampling effort with respect to our study, both in the number of sampling campaigns (between 14 and 15 in Brazil, two in the present study) and in the number of people involved in the samplings (five collectors in Brazil, two collectors in the present study), the species accumulation models showed both parks are close to a saturation point, indicating there is a realistic species richness difference between the areas involved (temperate Europe vs. neotropical Brazil).…”
Section: Discussionmentioning
confidence: 99%
“…The authors working on terrestrial flatworm’s ecology (see Baptista & Leal‐Zanchet, 2010; Baptista et al., 2006; Carbayo et al., 2002; De Castro & Leal‐zanchet, 2005; Fick et al., 2006; Leal‐Zanchet et al., 2011) used plots of fixed sizes (50 × 2 m, 2 × 2 m, 7 × 7 m) or transects of fixed length (30 to 50 m) as a sampling unit. On each plot or transect, the sampling methodology used was always direct searching by a fixed number of researchers (between one and five) during a standardized lapse of time (between 15 min and 1 hr).…”
Section: Methodsmentioning
confidence: 99%
“…Freshwater and land triclads were studied mainly in the Brazilian states of São Paulo and Rio Grande do Sul (Carbayo and Froehlich, 2008;Baptista et al 2010;Leal-Zanchet et al, 2011;Amaral et al, 2014). Polyclads were mainly known from the coast of the states of São Paulo and Rio de Janeiro, as well as the northeastern coast of Brazil (Carbayo and Froehlich, 2008;Bahia and Padula, 2009;Bahia et al, 2012;Bulnes and Torres, 2014).…”
Section: Introductionmentioning
confidence: 99%